Pre‐incubation of corneal donor tissue with sCD83 improves graft survival via the induction of alternatively activated macrophages and tolerogenic dendritic cells. Issue 2 (20th September 2021) - Peckert‐Maier, Katrin; Schönberg, Alfrun; Wild, Andreas B.; Royzman, Dmytro; Braun, Gabriele; Stich, Lena; Hadrian, Karina; Tripal, Philipp; Cursiefen, Claus; Steinkasserer, Alexander; Zinser, Elisabeth; Bock, Felix
Abstract : Immune responses reflect a complex interplay of cellular and extracellular components which define the microenvironment of a tissue. Therefore, factors that locally influence the microenvironment and re‐establish tolerance might be beneficial to mitigate immune‐mediated reactions, including the rejection of a transplant. In this study, we demonstrate that pre‐incubation of donor tissue with the immune modulator soluble CD83 (sCD83) significantly improves graft survival using a high‐risk corneal transplantation model. The induction of tolerogenic mechanisms in graft recipients was achieved by a significant upregulation of Tgfb, Foxp3, Il27, and Il10 in the transplant and an increase of regulatory dendritic cells (DCs), macrophages (Mφ), and T cells (Tregs) in eye‐draining lymph nodes. The presence of sCD83 during in vitr o DC and Mφ generation directed these cells toward a tolerogenic phenotype leading to reduced proliferation‐stimulating activity in MLRs. Mechanistically, sCD83 induced a tolerogenic Mφ and DC phenotype, which favors Treg induction and significantly increased transplant survival after adoptive cell transfer. Conclusively, pre‐incubation of corneal grafts with sCD83 significantly prolongs graft survival by modulating recipient Mφ and DCs toward tolerance and thereby establishing a tolerogenic microenvironment. This functional strategy of donor graft pre‐treatment paves the way for new therapeutic options in the field of transplantation. Abstract : Antigen‐presenting cells improve long‐term corneal graft survival when donor tissue is pre‐incubated with immune modulatory sCD83.